Tasks and Principles of International Cooperation in the Field of Forensic Examination - I. I. Yatsenko (Bulletin of Kharkiv National University of Internal Affairs)
The basic categories: “tasks”, “principles”, “forensic examination”, “international cooperation” have been studied. The legal regulation of international cooperation in the field of forensic examination has been determined. The understanding of the category of “tasks and principles of international cooperation in the field of forensic examination” has been clarified.